Alterations on blood pressure and glycemia between education (Research, Society and Development, 2021)
Objective: to describe the cases of changes in blood pressure and capillary glycemia among university education workers. Methodology: observational, sectional descriptive epidemiological study. Data collection took place during 2018. The study sample consisted of university college workers. The total number of participants was 106 professionals. Results: among the employees, 47 (44.9%) had altered blood pressure, and 12 (11.3%) had high blood glucose. In the bivariate analysis, between blood pressure and sociodemographic, occupational and health aspects, an association was observed between males (p = 0.007), age above the mean of 38 years (p = 0.005), time in the sector above 4 years (p = 0.004), high abdominal circumference (p = 0.009) and overweight and obesity (p = 0.001). There was no statistical significance between capillary blood glucose and the variables investigated. Conclusion: male gender, age, abdominal circumference and overweight stand out as characteristics that are related to high blood pressure levels. Measures to promote health and quality of life should be encouraged among the group of workers.